O Luto em Portugal: da Corte à Gente Comum (séculos XV-XVI) - Ana Mafalda Pereira Lopes (Medievalista)
The following study casts a brief look at the rituals of mourning within the perspective of the History of the Emotions, a recent but relevant historical field that intends to interpret under a new light habits and actions from the past. We will analyze the concepts and practices of mourning and their evolution throughout the Early Modern period, by reviewing the contents mainly of royal chronicles, inserting the narratives of mourning in their political contexts. Our study suggests that, at least among court circles, there was a tendency towards the privatization of pain, through the progressive disappearance of violent expressions of emotion, while the latter remained mostly unaltered among the common people.